2010
DOI: 10.1089/ten.tea.2009.0226
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assessment of Skeletal Muscle Regeneration Utilizing Homologous Extracellular Matrix as Scaffolding

Abstract: The loss of a portion of skeletal muscle poses a unique challenge for the normal regeneration of muscle tissue. A transection injury with tissue loss will not heal due to the gap between muscle segments. A damage model was developed by removing a portion of the lateral gastrocnemius (GAS) of Sprague-Dawley rats. Maximal isometric, tetanic tension (P(o)) was measured after the removal of either a small defect (0.5 x 1.0 cm) or a large defect (1.0 x 1.0 cm) piece of the GAS. In situ P(o) immediately after creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 42 publications
8
133
1
Order By: Relevance
“…Acquired muscle affections are seemingly more common in active humans, greatly associated to sports practice, but also quite frequent in other traumatic sceneries, such as road or workrelated accidents or war injuries [8][9][10][11]. Muscle damage can result from ischemia and denervation, to contusion, sprain damage, laceration, avulsion, and other severe tissue losses.…”
Section: Introductionmentioning
confidence: 99%
“…Acquired muscle affections are seemingly more common in active humans, greatly associated to sports practice, but also quite frequent in other traumatic sceneries, such as road or workrelated accidents or war injuries [8][9][10][11]. Muscle damage can result from ischemia and denervation, to contusion, sprain damage, laceration, avulsion, and other severe tissue losses.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other studies have indicated the possibility to use decellularized tissue scaffolds also for skeletal muscle repair and adipose-tissue engineering (L. Flynn et al, 2007;L.E. Flynn, 2010;Gillies et al, 2010;Merritt et al, 2010).…”
Section: Reprocessed Tissue Scaffoldsmentioning
confidence: 96%
“…Several studies have shown that fibrin glue can provide sustained release of GFs during a few days to one week (Spicer & Mikos, 2010). Longer GF retention times can be achieved by modifications in the GF (Schmoekel et al, 2004), by integrating high GF-affinity moieties in the fibrin chains (Merritt et al, 2010), or by covalent linking of the GFs (Drinnan et al, 2010;Schmoekel et al, 2005). Examples of GFs that have been integrated in fibrin gels in skeletal tissue engineering applications include BMP-2 (Kang et al, 2011;Schmoekel et al, 2004;Schmoekel et al, 2005), TGF-1 and TGF-3 (Drinnan et al, 2010;W.…”
Section: Fibrinmentioning
confidence: 99%
“…Hematoxylin & eosin (H&E) staining was performed as previously described [28], and slides were observed with a light microscope (Nikon Diaphot, Nikon Corp., Tokyo, Japan) with the 20× objective lens. Images were taken using a mounted digital camera (Optronix Microfire; Optronix, CA, USA).…”
Section: Histology and Immunofluorescencementioning
confidence: 99%
“…Calf muscles were surgically exposed and subjected to in situ functional measurements [28]. The Achilles tendon was tied to the muscle lever arm of a servomotor (model 305B, Cambridge Technologies) interfaced with a computer equipped with an A/D board (National Instruments).…”
Section: Skeletal Muscle Contractile Studiesmentioning
confidence: 99%